PENINGKATAN PENGETAHUAN MASYARAKAT MELALUI EDUKASI TENTANG APLIKASI AGROFORESTRI UNTUK MENDUKUNG SISTEM PERTANIAN BERKELANJUTAN DESA LAKAMBARA KAB. KONAWE SELATAN - Vivi Fitriani; Kahirun Kahirun; La Baco Sudia; La Ode Midi (Universitas Halu Oleo, 2022)
The management of agricultural land that is still conventional and the lack of information related to land management has caused the condition of several agricultural lands in Lambakara Village to be quite concerning. The condition of Lambakara Village which is directly adjacent to the village with hilly topography and steep slopes can cause Lambakara Village to be prone to landslides and flooding. In addition, the quality and quantity of soil can decrease as a result of long-term agricultural management. One alternative to overcome the problems faced by Lambakara Village is the application of the Agroforestry system. the purpose of this service is to provide knowledge and learning to farmers as an effort to increase public knowledge about agroforestry applications. The initial stage was carried out in the form of a location survey stage to find out which community lands could be used and have the potential to implement the Agroforestry system. The socialization stage was in the form of interviews and coordination with village officials, related stakeholders, and the community in introducing the Agroforestry system as an effort to conserve agricultural land to support sustainable agriculture. The implementation stage is in the form of public education regarding the Agroforestry system and direct planting of forestry plants on community agricultural land. All stages of community service activities in Lambakara Village were carried out well. The involvement of village officials and the local community is the main indicator of achieving the target of this activity. As many as 300 nutmeg seedlings were successfully planted on the community's agricultural land